2013
DOI: 10.1371/journal.pone.0068262
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Weaning Growth Hormone Treatment Ameliorates Bone Marrow Macrophage Inflammation in Adult Male Rat Offspring following Maternal Undernutrition

Abstract: Maternal undernutrition (UN) is associated with the development of obesity and metabolic complications in adult offspring. While the role of inflammation in obesity and related comorbidities has been well established, there is little evidence regarding the effects of maternal UN-induced programming on immune function in male adult offspring. This study examines the effects growth hormone (GH), which is known to induce anti-inflammatory effects, on maternal UN-induced bone marrow macrophage (BMM) function in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Adverse early life events can lead to offspring long-term health problems. Several studies have shown that intervention during this critical period can have potentially long-term benefit for the offspring [21,22,[51][52][53]. The present study shows that taurine supplementation reversed fructose-induced male offspring hepatic PEPCK, which potentially prevented maternal-programming-initiated predisposition to dysregulated glucose metabolism.…”
Section: Discussionsupporting
confidence: 55%
“…Adverse early life events can lead to offspring long-term health problems. Several studies have shown that intervention during this critical period can have potentially long-term benefit for the offspring [21,22,[51][52][53]. The present study shows that taurine supplementation reversed fructose-induced male offspring hepatic PEPCK, which potentially prevented maternal-programming-initiated predisposition to dysregulated glucose metabolism.…”
Section: Discussionsupporting
confidence: 55%
“…It has also been reported that prenatal dexamethasone exposure in female offspring weaned onto the high-fat diet potentiates hepatosteatosis and inhibits the GH axis function, because it induces a decrease of plasma IGF-I concentrations and in the hypothalamic GHRH mRNA [132]. The involvement of these changes in growthrelated hormones is further supported by a study showing that pre-weaning GH treatment reverses hypertension and endothelial dysfunction in adult male offspring of mothers undernourished during pregnancy [133].…”
Section: Growth Related Hormones and Metabolic Alterationsmentioning
confidence: 85%
“…Some studies have suggested the compensatory effects of prenatal undernutrition with adequate postnatal nutrition or hormonal therapy (Reynolds et al 2013;Wattez et al 2014), whereas other authors remain quite pessimistic. Animal research shows that a spare diet from a young age might be helpful in preventing age induced damage on pancreatic β cells (He et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies describe a wide range of possible metabolic alterations as a result of an insufficient diet during pregnancy. These include small birth weight (Frederick et al 2008;Pinheiro et al 2008;Yu et al 2013), delayed maturation (van Weissenbruch et al 2005;Guzman et al 2006), altered endocrine and nervous regulation of metabolism (McArdle et al 2006;Sellayah et al 2008;Coupe et al 2010;Myles et al 2011;Peixoto-Silva et al 2011;Reusens et al 2011a, b;de Oliveira et al 2012;Garcia et al 2013), obesity (Hoffman et al 2000;Kinra et al 2000;Ozanne and Hales 2004;Yajnik 2004;Varela-Silva et al 2007), inadequate immune response (Beach et al 1982;Reynolds et al 2013), greater risk of non-communicable diseases in adulthood (Benyshek et al 2006; Kyle and Pichard 2006;Koupil et al 2007;Torrens et al 2008;Harrison and Langley-Evans 2009;Hult et al 2010;Norman et al 2012;Ponzio et al 2012) as well as changes in cognitive function (Blaise et al 2007;Gilbert et al 2010;Zhang et al 2010;Ito et al 2011) or even circadian rhythms (Orozco-Solis et al 2011). However, this subject is rarely examined through a lifetime, and only a glimpse of possible consequences is traced.…”
Section: Introductionmentioning
confidence: 99%